2019
DOI: 10.1007/978-3-030-20883-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Does FLOSS in Software Engineering Education Narrow the Theory-Practice Gap? A Study Grounded on Students’ Perception

Abstract: Software engineering education is challenged by the need to convey practical experience in the context of a rich and large body of theoretical knowledge. This study investigates whether the use of open source projects can reduce the gap between theory and practice in undergraduate software engineering courses. Two qualitative case studies were conducted with students performing activities in an open source project, each one in a different course: software testing and software requirements. Results point out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
1
12
0
3
Order By: Relevance
“…A promising approach for bridging the gap between academia and industry is the integration of open-source development into the software engineering or computer science curriculum. A recent study confirmed that the use of open-source projects in the classroom provides a concrete experience similar to industry experience [19]. In the systematic mapping study performed by Nascimento et al [11], a total of 72 articles were reviewed in order to analyze the extent and range of previous research relating to the use of opensource projects in software engineering education.…”
Section: Related Workmentioning
confidence: 94%
See 2 more Smart Citations
“…A promising approach for bridging the gap between academia and industry is the integration of open-source development into the software engineering or computer science curriculum. A recent study confirmed that the use of open-source projects in the classroom provides a concrete experience similar to industry experience [19]. In the systematic mapping study performed by Nascimento et al [11], a total of 72 articles were reviewed in order to analyze the extent and range of previous research relating to the use of opensource projects in software engineering education.…”
Section: Related Workmentioning
confidence: 94%
“…Researches such as the ones conducted by Ellis et al [13,24] analyze the impact of learning activities with Humanitarian Free and Open Source Software (HFOSS) projects in terms of motivation, learning experience, and career plans. Other studies describe courses where students take different roles (e.g., developers, testers, requirements definition engineers) in real open source project developments [7,19,25]. Researches, such as the one conducted by Braught et al, compare the methodology followed by different universities and colleges in courses and capstone projects offered to undergraduate students [12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…I u naučno istraživačkom radu se sve više naučnih članaka objavljuje pod nekom od Open Source licenci kako bi bila dostupna većem broju istraživača, ali i samom autoru obezbedila veću vidljivost kroz citiranost tih radova. [11] Sa porastom popularnosti softvera otvorenog koda [36] i srodnih trendova, kultura otvorenosti napreduje od ivica društva do srži akademske kulture. [12] Jedan od primera akademske kulture otvorenosti znanja je Univerzitet Singidunum, Beograd, Srbija [13] koji ima portal na kome su besplatno dostupna sva univerzitetska izdanja knjiga, i svih ostalih naučnih članaka kako profesora tako i studenata.…”
Section: Prednosti Korišćenja Otvorenog Pristupa U Obrazovanjuunclassified
“…During the last 20 years, Software Engineering (SE) instructors have proposed the study and development of open source/free/libre software (abbreviated as OSS, FLOSS, or FOSS) projects to introduce students into real-world examples of SE principles, concepts and practices [1][2][3]. Mature OSS projects are considered more realistic than examples found in textbooks or developed by teaching staff [2,4]. These projects are usually complex and large, with many developers involved, responding to real-world needs and problems and are built following software engineering best practices.…”
Section: Introductionmentioning
confidence: 99%